Accountability and Reform in the Aftermath of the Westray Mine Explosion - Tucker, Eric (Working Disasters: The Politics of Recognition and Response, 2006)
This edited collection draws together original case studies written by leading researchers in Australia, Canada, Great Britain, Sweden, and the United States that examine the politics of working disasters. The essays address two fundamental questions: what gets recognized as a work disaster? And how does the state respond to one? –Publisher's description. Contents: Introduction: The Politics of Recognition and Response / Eric Tucker – Trucking Tragedies: The Hidden Disaster of Mass Death in the Long-Haul Road Transport Industry / Michael Quinlan, Claire Mayhew, and Richard Johnstone – The Australian Epidemic of Repetition Strain Injury: A Sociological Perspective / Andrew Hopkins – "All Part of the Game": The Recognition of and Response to an Industrial Disaster at the Fluorspar Mines, St Lawrence, Newfoundland, 1933-1978 / Richard Rennie – The Long Road to Action: The Silicosis Problem and Swedish Occupational Health and Safety Policy in the 20th Century / Annette Thörnquist – Disaster, Meaning Making, and Reform in Antebellum Massachusetts / Patricia Reeve – Regulating Safety, Regulating Profit: Cost-Cutting, Injury and Death in the British North Sea after Piper Alpha / Dave Whyte – Courts, Crime, and Workplace / Richard Johnstone – Blame and Causation in the Aftermath of Industrial Disasters: Nova Scotia's Coal Mines from 1858 to Westray / Susan Dodd – Accountability and Reform in the Aftermath of the Westray Mine Explosion / Eric Tucker.
https://archive.org/details/workingdisasters0000unse
Keywords: Government policy; Industrial accidents; Industrial safety; Occupational diseases

Introduction: The Politics of Recognition and Response - Tucker, Eric (Working Disasters: The Politics of Recognition and Response, 2006)
This edited collection draws together original case studies written by leading researchers in Australia, Canada, Great Britain, Sweden, and the United States that examine the politics of working disasters. The essays address two fundamental questions: what gets recognized as a work disaster? And how does the state respond to one? –Publisher's description
https://archive.org/details/workingdisasters0000unse
Keywords: Government policy; Industrial accidents; Industrial safety; Occupational diseases

Caught in the Machinery: Workplace Accidents and Injured Workers in Nineteenth-Century Britain - Tucker, Eric (Labour / Le Travail, 2008)
The article reviews the book, "Caught in the Machinery: Workplace Accidents and Injured Workers in Nineteenth-Century Britain," by Jamie L. Bronstein.
Keywords: BOOKS – Reviews; BRONSTEIN; Jamie L.; CAUGHT in the Machinery: Workplace Accidents & Injured Workers in 19th-Century Britain (Book); Nonfiction; WORK-related injuries

The Constitutional Right to Bargain Collectively: The Ironies of Labour History in the Supreme Court of Canada - Tucker, Eric (Labour / Le Travail, 2008)
The article focuses on the constitutional right to bargain collectively in Canada. Employers in Canada have adopted labour management policies that including resistance to and avoidance of collective bargaining, shifting from secure employment forms and increasing demand on the workforce. It mentions the Hospital Employees' Union (HEU) which had successfully fought a long battle to achieve pay equity for its largely female membership.
Keywords: Canada; Collective bargaining; Collective labor agreements; Employers; HOSPITAL personnel – Salaries; etc.; Labor Unions

The Accidental Republic: Crippled Workingmen, Destitute Widows, and the Remaking of American Law - Tucker, Eric (Labour / Le Travail, 2005)
The article reviews the book, "The Accidental Republic: Crippled Workingmen, Destitute Widows, and the Remaking of American Law," by John Fabian Witt.

Diverging Trends in Worker Health and Safety Protection and Participation in Canada, 1985-2000 - Tucker, Eric (Relations Industrielles / Industrial Relations, 2003)
Despite the comprehensiveness of neo-liberal restructuring in Canada, it has not proceeded uniformly in its timing or outcomes across regulatory fields and political jurisdictions. The example of occupational health and safety (OHS) regulation is instructive. This article compares recent OHS developments in five Canadian jurisdictions, Alberta, British Columbia, Nova Scotia, Ontario and the Federal jurisdiction. It finds that despite the adoption of a common model by all jurisdictions, there has recently been considerable divergence in the way that the elements of worker participation and protection have been combined. Modified power resource theory is used to explain a portion of this divergence.
Keywords: Canada; INDUSTRIAL hygiene – Law & legislation; Industrial safety; Jurisdiction; OCCUPATIONAL health services

Pluralism or Fragmentation?: The Twentieth-Century Employment Law Regime in Canada - Fudge, Judy; Tucker, Eric (Labour / Le Travail, 2000)
In 1947. Bora Laskin, the doyen of Canadian collective bargaining law, remarked that "Labour relations as a matter for legal study … has outgrown any confinement to a section of the law of torts or to a corner of the criminal law. Similarly, and from another standpoint, it has burst the narrow bounds of master and servant." That standpoint was liberal pluralism, which comprises collective bargaining legislation administered by independent labour boards and a System of grievance arbitration to enforce collective agreements. After World War II, it came to dominate our understanding of labour relations law such that, according to Laskin, reference to "pre-collective bargaining standards is an attempt to re-enter a world that has ceased to exist." But this picture is only partially true. Instead of replacing earlier regimes of industrial legality, industrial pluralism was grafted on to them. Moreover, it only encompassed a narrow, albeit crucial, segment of workers; in the mid-1950s "the typical union member was a relatively settled, semi-skilled male worker within a large industrial corporation." More than 65 per cent of Canadian workers at that time, a large proportion of whom were women and recent immigrants, fell outside the regime. This paper broadens the focus from collective bargaining law to include other forms of the legal regulation of employment relations, such as the common law, minimum standards, and equity legislation. In doing so, it examines the extent to which liberal pluralism regime was implicated in constructing and reinforcing a deeply segmented labour market in Canada. It also probes whether the recent assault on trade union rights may be the trajectory for the reconstruction of a new regime of employment relations.

Labour Before the Law: The Regulation of Workers' Collective Action in Canada, 1900-1948 - Fudge, Judy; Tucker, Eric (Oxford University Press, 2001)
In this study of the relations between workers and the state, Judy Fudge and Eric Tucker examine the legal regulation of workers' collective action from 1900 to 1948. They analyze the strikes, violent confrontations, lockouts, union organizing drives, legislative initiatives, and major judicial decisions that transformed the labour relations regime of liberal voluntarism, which prevailed in the later part of the nineteenth century, into industrial voluntarism, whose centrepiece was Mackenzie King's Industrial Disputes Investigation Act of 1907. This period was marked by coercion and compromise, as workers organized and fought to extend their rights against the profit-oriented owners of capital, while the state struggled to define a labour regime that contained industrial conflict. The authors then trace the conflicts that eventually produced the industrial pluralism that Canadians have known in more recent years." "The book is simultaneously & history of law, aspects of the state, trade unions and labouring people, and their interaction within the broad and shifting terrain of political economy. The authors are attentive to regional differences and sectoral divergences, and they attempt to address the fragmentation of class experience. – Publisher's description
Book available at Internet Archive to readers with print disabilities: https://archive.org/details/labourbeforelawr0000fudg
Keywords: 20e siecle. Travail; 20th century. Syndicats; Canada; Droit; Histoire; History; Labor Unions; Law and legislation

The Freedom to Strike in Canada: A Brief Legal History - Fudge, Judy; Tucker, Eric (Canadian Labour & Employment Law Journal, 2009)
This paper looks at the “deep roots” of striking as a social practice in Canada, by providing an analytic framework for approaching the history of the right to strike, and then sketching the contours of that history. Focusing on the three key worker freedoms — to associate, to bargain collectively, and to strike — the authors trace the jural relations between workers, employers and the state through four successive regimes of industrial legality in Canada: master and servant; liberal voluntarism; industrial voluntarism; and industrial pluralism, the latter marked by the adoption of the Wagner Act model. On the basis of their review of those regimes, the authors argue that long before the modern scheme, workers enjoyed a virtually unlimited freedom to strike for collective bargaining purposes. Although government-imposed restrictions on the freedom have increased significantly, especially under industrial pluralism, legislatures have typically provided workers with compensating trade-offs, including rights enforceable against their employers. However, in contrast to the historical pattern, public-sector workers have with growing frequency been subjected to “exceptionalism,” i.e. the suspension or limitation of freedoms without a grant of compensatory rights. In the authors’ view, it is the imposition of such measures that will likely provide the context for consideration of whether the Canadian Charter of Rights and Freedoms protects the right to strike.

Will the Vicious Circle Be Unbroken? The Exclusion of Ontario Farm Workers from the Occupational Health and Safety Act - Tucker, Eric (Precarious Employment: Understanding Labour Market Insecurity in Canada, 2006)
[The author] critically examines the rationale offered to justify the exclusion of agricultural workers from occupational health and safety legislation [in Ontario] which lasted until 2005. The chapter is a case study of marginalized workers denied the benefit of labour law protections. –From editor's introductory chapter, p. 38.
https://www.mqup.ca/precarious-employment-products-9780773529618.php
Keywords: Labor Unions; Labor laws and legislation; Labor market; Temporary employment

All That is Solid Melts into Air: Worker Participation and Occupational Health and Safety Regulation in Ontario, 1970-2000. - Storey, Robert; Tucker, Eric (Worker Safety under Siege: Labor, Capital, and the Politics of Workplace Safety in a Deregulated World, 2006)
"[P]rovides a historical analysis of worker participation and occupational health and safety regulation in Ontario from 1970 to 2000 in light of the rise of neoliberal policies. [The authors] describe a shift from systems of mandated partial self-regulation in which workers had to participate, supported by external enforcement of regulations, to more ambiguous models that included the downsizing of government and voluntary compliance by employers." –Editors' introduction. Contents: Acts of God, acts of man: the invisibility of workplace death / Jordan Barab – Criminal neglect: how dangerous employers stay safe from prosecution / Rory O'Neill – Regulating risk at work: is expert paternalism the answer to workers irrationality? / Peter Dorman – Silicosis and the on-going struggle to protect workers's health / Gerald Markowitz and David Rosner – How safe are U.S. workplaces for Spanish-speaking workers? / Laura H. Rhodes – Got air? The campaign to improve indoor air quality at the City University of New York / Joan Greenbaum and David Kotelchuck – State or society? The rise and repeal of OSHA's ergonomics standard / Vernon Mogensen – The ten-percenters: gender, nationality, and occupational health in Canada / Penney Kome – All that is solid melts into air: worker participation in Ontario, 1970-2000 / Robert Storey and Eric Tucker – The sinking of the neoliberal P-36 platform in Brazil / Carlos Eduardo Siqueira and Nadia Haiama-Neurohr – Health and safety at work in Russia and Hungary: illusion and reality in the transition crisis / Michael Haynes and Rumy Husan.
Keywords: Industrial hygiene; Industrial safety

Self-Employed Workers Organize: Law, Policy, and Unions - Cranford, Cynthia; Fudge, Judy; Tucker, Eric; Vosko, Leah F. (McGill-Queen's University Press, 2005)
Over a million self-employed Canadians work every day but many of them are not entitled to the basic labour protections and rights such as minimum wages, maternity and parental leaves and benefits, pay equity, a safe and healthy working environment, and access to collective bargaining. The authors of "Self-Employed Workers Organize" offer a multi-disciplinary examination of the legal, political, and social realities that both limit collective action by self-employed workers and create huge impediments for unions attempting to organize them. Through case studies of newspaper carriers, rural route mail couriers, personal care workers, and freelance editors - four groups who have led pioneering efforts to organize - the authors provide a window into the ways political and economic conditions interact with class, ethnicity, and gender to shape the meaning and strategies of working men and women and show how these strategies have changed over time. They argue that the experiences of these workers demonstrate a pressing need to expand collective bargaining rights to include them. –Publisher's description
Book available at Internet Archive to readers with print disabilities: https://archive.org/details/selfemployedwork0000unse
Keywords: Case studies; Labor unions; Legal status; laws; etc.; Organizing; Self-employed

Precarious Employment and the Law's Flaws: Identifying Regulatory Failure and Securing Effective Protection for Workers - Bernstein, Stephanie; Lippel, Katherine; Tucker, Eric; Vosko, Leah F. (Precarious Employment: Understanding Labour Market Insecurity in Canada, 2006)
This chapter is concerned wtih identifying the many symptoms associated with the inadequacy of workers' protection that the study of precarious employment makes visible. ...[The authors] probe key themes central to regulatory failure in the context of precarious employment, including disparity of treatment between workers in precarious employment and workers with greater security, gaps in legal coverage, the interaction between labour market position and social location, and the lack of compliance and enforcement. –From editor's introductory chapter, p. 37.
Keywords: Labor Unions; Labor laws and legislation; Labor market; Temporary employment